KAJIAN PENGEMBANGAN AGROFORESTRI UNTUK PENGELOLAAN DAERAH ALIRAN SUNGAI TORANDA, KECAMATAN PALOLO, KABUPATEN SIGI, PROPINSI SULAWESI TENGAH - Danang Widjajanto; Rosmaniar Gailea (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The objectives of the research were to analyze dominant factors affecting community preference on agroforestry development; to determine the commodity priority on agroforestry development; to analyze the financial feasibility of cocoa monoculture and agroforestry farming system; to estimate soil erosion rate on different land use. The research was conducted at the Micro Watershed Model of Toranda, Palolo District, Sigi Regency, Central Sulawesi Province. Social-economic survey of the local community and soil erosion aimed to analyze community perception, financial feasibility of farming systems, and land conversion impact on land degradation caused by erosion. The results of the research showed that the dominant factors affected the community preference on agroforestry development were farming system capitals, financial profit, land suitability, erosion control and land rehabilitation, agribusiness partnership, and farmer institution role. The community preference on prioritiy commodity development was in order of (Tectona grandis), mahoni (Switenia macrophylla), nyatoh (Palaquium sp.), cempaka (Michelia campaka), Ebony (Diospyros celebica), candle nut (Aleurites mollucana), and avocado (Persea americana), respectively.  The cocoa monoculture and agroforestry farming systems are feasible to be developed. The benefit-cost ratio (BCR) and Internal Rate of Return (IRR) of cocoa monoculture farming systems are 3.01 and 0.35, respectively, and agroforestry farming systems of cocoa are 4.59 and 0.40, respectively. Finally, the soil erosion rate of cocoa monoculture farming systems at 9 % slope and cocoa agroforestry farming systems at 9 % and 38 % slopes are lower than the tolerable soil loss (TSL), whiles the soil erosion of cocoa monoculture farming systems at 38 % slope and bare soil at 5 % slope are higher than the tolerable soil loss (TSL)